Comparative Evaluation of Tomato Hybrids and Parental Lines For Fruit Quality Traits - Nimit Singh,; Ashish Kumar Singh,; R.B Singh,; antosh Kumar,; Akhil Kumar chaudhary,; Virender Kumar,; Shyam Prakash,; Suman Poonia, (The Bioscan, 2025)
The present study was conducted to assess the variability and performance of tomato (Solanum lycopersicum L.) parental lines and their hybrids for key quality traits. Eleven genetically diverse parental lines were crossed and the resulting hybrids were evaluated along with their parents for seven traits: total soluble solids (TSS), total sugars, titratable acidity, ascorbic acid, lycopene, total carotenoids, and total phenolic content. Significant variability was observed among genotypes for all traits, indicating ample scope for genetic improvement.